Odpowiedź :
Odpowiedź:
[tex]a)\ \ 7-\frac{5}{9}=6\frac{9}{9}-\frac{5}{9}=6\frac{4}{9}\\\\b)\ \ 3\frac{1}{7}-1\frac{3}{4}=3\frac{4}{28}-1\frac{21}{28}=2\frac{32}{28}-1\frac{21}{28}=1\frac{11}{28}\\\\c)\ \ 3\frac{5}{12}-2\frac{2}{9}=3\frac{15}{36}-2\frac{8}{36}=1\frac{7}{36}[/tex]
a) 7= 63/9
63/9 - 5/9 = 58/9 = 6 4/9
b) 3 1/7 = 22/7
1 3/4 = 7/4
wspólny mianownik: 28
88/28 - 49/28 = 39/28 = 1 11/28
c) 3 5/12 = 41/12
2 2/9 = 20/9
wspólny mianownik: 36
123/36 - 80/36 = 43/36 = 1 7/36
mysle ze pomogłem :D